Heritability of serum dehydroepiandrosterone sulphate levels and pubertal development in 6∼18-year-old girls: a twin study - Hongjuan Li; Chengye Ji; Liu Yang; Cheng Zhuang (Taylor & Francis Group, 2017)
Background: Dehydroepiandrosterone sulphate (DHEAS), the most plentiful circulating adrenal hormone, may be considered as a marker of the onset of adrenarche and is involved in pubertal development and metabolic disorders. Aim: The objective of this study is to determine the genetic and environmental influences on the variation of basal DHEAS levels and pubertal development in pubertal girls. Subjects and methods: Three hundred and sixty twin girls aged 6-18-years were enrolled, consisting of 132 monozygotic pairs and 48 dizygotic pairs. Anthropometric and sexual characteristics were examined. Serum DHEAS was measured by RIA. Estimates of genetic and environmental components of variance were based on the theory of normal maximum likelihood in Mx package. Results: Serum DHEAS concentrations of PH-II and PH-III were significantly higher than Tanner stage PH-I (p < .05) and maintained higher levels in PH-IV ∼ V. Heritability of serum DHEAS estimated by model-fitting on data from 180-pairs of twins is 0.61 (0.52-0.70), the rest of the variance in DHEAS levels could be explained by unique environmental influences and age. The heritabilities of DHEAS in two pubertal sub-groups (PH-I and PH-II-V) are 0.82 (0.71-0.90) and 0.63 (0.52-0.74), respectively. The heritability index of menarche, breast development and pube development are 0.71, 0.35 and 0.45, respectively. Conclusions: Serum DHEAS concentrations of pubertal girls are mainly influenced by genetic factors, especially during the period of adrenarche. The results stress the importance of research into the genetic regulation of the endocrine regulators involved in adrenarche and related metabolic disorders in girls.